Fourth Order Runge-Kutta Method for Solving First-order Fully Fuzzy Differential Equations Under Strongly Generalized H-differentiability - Vivek, D.; Kanagarajan, K.; Indirakumar, S. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we use fourth order Runge-Kutta method for solving fully fuzzy differential equations of the form y'(t) = a⊗y(t), y(0)= y0, t ∈ [0,T] under strongly generalized H-differentiability. The algorithm used here are based on cross product of two fuzzy numbers. Using cross product we can divide fully fuzzy differential equation (FFDE) into four different cases. We apply the results to a particular case of FFDE. The Convergence of this method is discussed and numerical examples are given to verify the reliability of this method.